Analysis of the ships’s bow to minimise air pollution – case study of the X-bow ship - Tima Said Hamisi; Fadhloon Mwenye Ali; Talib Ibrahim Mohammed; Charles Gathua (Journal of International Maritime Safety, Environmental Affairs, and Shipping, 2023)
ABSTRACTAir pollution is a major concern in the maritime industry because of its negative health impacts and greenhouse gas emission. Reducing the friction and resistance on the hull of a marine vessel improves the efficiency. It also reduces fuel consumption and carbon emissions in the atmosphere. Researches show that the design of the forward part of the hull has an effect on the total hull resistance. This paper explains how to reduce air pollution from an X-bow ship by analysing the ship’s bow and making essential modifications. The analysis of the front section of an X-bow ship demonstrated how the flare angle and stem angle have an effect on the total hull resistance. The model of the ship was created by using the Rhinoceros software, and the CFD analysis was done in Autodesk CFD software. Based on the results, it was found that the X-bow model of (10° stem, 10°flare) has optimal ship performance between the range speed of 8-14 knots as compared with the original X-bow ship of (6° stem, 21° flare). The new model (10° stem, 10°flare) requires an Effective Horse Power (EHP) of 2847.97 HP which is much lower than the power of the original model,3947.56HP.